Establishing enforcement legitimacy in the pursuit of rule-breaking 'global elites': The case of transnational corporate bribery. (August 2016) - Lord, Nicholas
This article develops an analytical framework for analysing the legitimacy of law enforcement responses towards rule-breaking 'global elites', in particular multi-national corporations implicated in transnational corporate bribery. While international anti-bribery laws and norms converge cross-jurisdictionally, enforcement contexts and responses can diverge formally creating dilemmas over how to establish the relative legitimacy of different enforcement frameworks. This article draws on a threefold framework proposed by David Beetham for understanding legitimacy (i.e. legality, normative validity, legitimation) which it considers in relation to the contingent cultural contexts of enforcement of two jurisdictions, Germany and the UK, before identifying key necessary minimum requirements of legitimate enforcement that can inform cross-cultural analysis. The article suggests the proposed framework provides an alternative to current evaluative measures used by international anti-corruption organizations.